2017
DOI: 10.1080/2162402x.2017.1375641
|View full text |Cite
|
Sign up to set email alerts
|

A bispecific nanobody approach to leverage the potent and widely applicable tumor cytolytic capacity of Vγ9Vδ2-T cells

Abstract: Though Vγ9Vδ2-T cells constitute only a small fraction of the total T cell population in human peripheral blood, they play a vital role in tumor defense and are therefore of major interest to explore for cancer immunotherapy. Vγ9Vδ2-T cell-based cancer immunotherapeutic approaches developed so far have been generally well tolerated and were able to induce significant clinical responses. However, overall results were inconsistent, possibly due to the fact that these strategies induced systemic activation of Vγ9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 67 publications
2
53
0
1
Order By: Relevance
“… 77 There are multiple strategies for the rational design of even smaller molecules, such as single-domain nanobodies with low immunogenicity that may increase the likelihood of accumulating around the actual tumor site for the activation of tumor-resident γδ T cells. 196 , 197 In preclinical proof-of-principle studies, the therapeutic efficacy of such anti-EGFR-Vγ9 nanobodies has been demonstrated, 198 and bispecific γδ T cell engagers are in development for targeting γδ T cells in cancer patients. Lava Therapeutics’ first bispecific γδ T cell engager (see Table 1 ) against a novel target is entering clinical trials with first patients with a hematological indication anticipated for the end of 2020 (P. Parren, personal communication).…”
Section: How To Activate and Target γδ T Cells In Vivomentioning
confidence: 99%
“… 77 There are multiple strategies for the rational design of even smaller molecules, such as single-domain nanobodies with low immunogenicity that may increase the likelihood of accumulating around the actual tumor site for the activation of tumor-resident γδ T cells. 196 , 197 In preclinical proof-of-principle studies, the therapeutic efficacy of such anti-EGFR-Vγ9 nanobodies has been demonstrated, 198 and bispecific γδ T cell engagers are in development for targeting γδ T cells in cancer patients. Lava Therapeutics’ first bispecific γδ T cell engager (see Table 1 ) against a novel target is entering clinical trials with first patients with a hematological indication anticipated for the end of 2020 (P. Parren, personal communication).…”
Section: How To Activate and Target γδ T Cells In Vivomentioning
confidence: 99%
“…This compound has shown a potent ability to activate Vγ9Vδ2 T cells and to induce their antitumoral activity in vitro and in mouse xenograft model in vivo independently on the mutational status of the tumor. Thanks to the conserved monomorphic nature of the Vγ9Vδ2 TCR that permits a more selective cell recruitment, this immunotherapeutic approach could be used in several different clinical settings and could be applied to a large group of cancer patients ( 117 ).…”
Section: Targeting Tme For Therapymentioning
confidence: 99%
“…Heavy-chain only antibodies (hcAbs) derived from camelids or sharks that devoid of light chains and lack CH1, nevertheless have an extensive antigen-binding repertoire, its variable domain were named VHH or nanobody (Nb) (15 kDa) [15][16][17][18]. Nanobody offer advantages including high affinity and specificity, smaller size (1/10th the size of conventional monoclonal antibodies), thermostability, low immunogenicity, and excellent tissue penetration-characteristics that are widely applied in oncotherapy, diagnosis and monitoring of disease, and prevent virus infection [19][20][21][22][23][24]. For example, numerous researches about Nbs antiviral activity for various challenging viruses have been reported, including MERS, HIV, HCV, IAV, SFTSV [24][25][26][27].…”
Section: Sars-cov-2 Is An Enveloped Virus That Belongs To the Family mentioning
confidence: 99%